Nutritional evaluation of the main commercial dog food in Metropolitan Lima - Chávez Matías, Nataly (2022)
The aim of this study was to contrast the results of the proximal analysis in the main dry balanced foods for puppies and adult dogs marketed in Lima, Peru, with those suggested by the Association of American Feed Control Officials (AAFCO) and with the nutritional content corresponding to the label of each brand. Sixteen samples from 10 brands of dry food for puppies and dogs were collected using an intentional non-probabilistic sampling design. The samples were sent to two animal nutrition laboratories (one laboratory analysed the puppy food samples and the other the adult dog samples) to determine the levels of protein, fat, fibre, ash and moisture. All samples showed on their label a guaranteed analysis as recommended by AAFCO; however, proximal chemical analysis showed some contradictions, as is the case of fat with levels below the minimum recorded on its labels and even the minimum recommended by AAFCO, both for puppy and adult foods, especially those categorized as economical. One of the eight brands of adult canine food had protein levels below the minimum recorded on its label, but all above the minimum suggested by the AAFCO. The fibre and moisture levels of all brands matched what was recorded on their labels. In conclusion, the dry balanced foods marketed in Metropolitan Lima and categorized as economical, both for puppies and adults, showed greater inconsistencies in the results of the proximal chemical analysis, mainly in fat levels, so they would be affecting the health and well-being of canine pets.